2015
DOI: 10.1111/jfpp.12680
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Sorption Isotherms and Thermodynamics of Intermediate Moisture Category Indian Milk Product Cham-cham

Abstract: Cham‐cham, a traditional Indian milk product prepared by heat and acid coagulation of milk, has a shelf life of a few days. Its storage stability could be studied by monitoring the changes in water activity at different temperatures and humidity. Hence, moisture sorption characteristics of cham‐cham were determined at three temperatures i.e., 5, 25 and 40C to obtain sorption isotherms. The data obtained were fitted to several models in which BET (Brunauer–Emmett–Teller), Modified Mizrahi and Henderson model ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
2
5
0
1
Order By: Relevance
“…This coincides with what Zuo et al. (2015) and Puri and Khamrui (2016) found in protein-rich matrices. They found that the trend for increased water sorption with increased temperatures is due to a complex association between food components and water vapor that can vary according to temperature and the value of a w .…”
Section: Resultssupporting
confidence: 90%
“…This coincides with what Zuo et al. (2015) and Puri and Khamrui (2016) found in protein-rich matrices. They found that the trend for increased water sorption with increased temperatures is due to a complex association between food components and water vapor that can vary according to temperature and the value of a w .…”
Section: Resultssupporting
confidence: 90%
“…Results indicate stronger interactions between the chhana kheer and water vapour at low moisture content, finally leading to large Q st values. Similar observations have been made by Deshmukh et al [3] in kalakand and Puri and Khamrui [7] in cham-cham.…”
Section: Isosteric Heat Of Sorptionsupporting
confidence: 90%
“…Water activity plays a vital role in spoilage of foods, determining the shelf-stability and deteriorative mechanisms in food systems. Several scientists have reported and ISSN: 2577-4182 published moisture sorption isotherms of various dairy products such as kalakand [4], banana shrikhand [5], bottle gourd burfi [6], cham-cham [7], sandesh powder [8], mexican mennonite-style cheese [9] and dietetic rabri [10] at various temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in the flour's hygroscopicity was observed when increasing temperature, which was evident in the a w intermediate region and more representative for the desorption process (Figure 2). This behaviour is attributed to the fact that a change in temperature changes the mobility of water molecules and consequently the thermodynamic equilibrium between the vapour phase and the adsorbed phases (Puri & Khamrui, 2016). As the temperature increases, the water molecules are activated due to an increase in the energy level, which become less stable and the bonds between them and the active sites of the product become easier to break (Flores-Andrade, Beristatin, Vernon-Carter, Gutiérrez, & Azuara, 2009).…”
Section: Flour Moisture Sorption Isothermsmentioning
confidence: 99%